2018
DOI: 10.1111/jicd.12338
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of double‐blind, placebo‐controlled, randomized clinical trials using probiotics in chronic periodontitis

Abstract: Adjunctive probiotics could result in additional benefits in CAL gain in CP. Nevertheless, further high-quality randomized clinical trials with microbiological outcomes are warranted to obtain strong conclusions in this regard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 34 publications
(146 reference statements)
3
49
0
5
Order By: Relevance
“…The potential application of probiotics has increasingly been advocated in periodontal care, but there is a dearth of evidence from double‐blind, paralleled‐arm, placebo‐controlled and randomized clinical trials that this study aimed to address (Ikram, Hassan, Raffat, Mirza, & Akram, ). The response rate in terms of attending all periodontal care sessions and all follow‐up assessments was high (at almost 90%, 52/59).…”
Section: Discussionmentioning
confidence: 99%
“…The potential application of probiotics has increasingly been advocated in periodontal care, but there is a dearth of evidence from double‐blind, paralleled‐arm, placebo‐controlled and randomized clinical trials that this study aimed to address (Ikram, Hassan, Raffat, Mirza, & Akram, ). The response rate in terms of attending all periodontal care sessions and all follow‐up assessments was high (at almost 90%, 52/59).…”
Section: Discussionmentioning
confidence: 99%
“… This is a gram‐negative anaerobic bacterium highly associated with periodontal disease and is considered a keystone pathogen in chronic periodontitis . In addition, systematic reviews and meta‐analysis support the use of L reuteri associated with conventional periodontal therapy, especially in deep pockets …”
Section: Introductionmentioning
confidence: 99%
“…The studies that evaluated the effects of probiotics on the treatment of periodontal disease demonstrated that they can reduce periodontopathogens, improve periodontal clinical parameters, decrease the levels of proinflammatory cytokines, and potentiate the effects of SRP Shah, Gujjari, & Chandrasekhar, 2013;Tekce et al, 2015;Teughels et al, 2013;Vivekananda, Vandana, & Bhat, 2010). In fact, two meta-analyses seem to support the adjunctive use of probiotics in the treatment of chronic periodontitis (Ikram, Hassan, Raffat, Mirza, & Akram, 2018;Martin-Cabezas, Davideau, Tenenbaum, & Huck, 2016). Nevertheless, further high-quality randomized clinical trials with microbiological outcomes are warranted to obtain strong conclusions in this regard (Ikram et al, 2018).…”
mentioning
confidence: 99%